ANALISIS KESESUAIAN PENGGUNAAN LAHAN PADA DAERAH RAWAN TANAH LONGSOR DI KABUPATEN TEGAL - Gilang Rupaka, Anggun Prima; Suharyanto, Suharyanto; Sudarno, Sudarno (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2015)
The frequency of landslides in Tegal regency increasing every year. The distribution area arealso more widespread, especially in districts Jatinegara, Bojong and Bumijawa. These regions has ahilly topography profile with a height ranging from 400 - 1200 meters above sea level. The landslideâ€™sfactors that use as the parameters in this study are rainfall, slope, soil type, depth of soil solum andland use. Suitability of land use based on the level of vulnerability to landslides associated with thelevel of capacity and vulnerability, because the area that not conform based on these factors are theresidential area.The method used to calculate and analyze the landslide-prone area in this study are with thehelp of GIS. The software were used to analyze consist of ArcGIS 10, ER Mapper 7.0 and Basemap.Satellite images digitized with ArcGIS to produce maps of land use. Then the land-use maps overlaidwith maps of slope, soil type maps, rainfall maps and depth of solum. Predefined values for eachparameter were then summed and classified based on assessment standards. The landslidesusceptibility map is then used to analyze the suitability of land in landslide-prone areas in Tegalregency. The level of capacity and vulnerability to disasters in areas prone to landslides obtained byinterview in the form of a questionnaire.Subdistrict Jatinegara, Bojong and Bumijawa has an area of 25.000 hectares, 37,81% of thearea that included in the "Landslide Prone" category, while the 59.82% of the area goes into the"Pretty-Prone Landslide" category. Conversion of forest land into agricultural production into is the oneof the factors that aggravate the landslide that happened. Villagers who live in landslide-prone areasdo not have the awareness that cutting down trees and intensive agriculture are causing landslidesthat in their area, in addition to soil type and slope factors that dominant. Vulnerability and capacity tolandslides in the region included in the low category. Factors that influence are economic level,education level, living conditions and the condition of the access road.Â